Assessing the co-benefits of urban greening coupled with rainwater harvesting management under current and future climates across USA cities. (28th February 2023) - Zhang, Ziyan; Dobson, Barnaby; Moustakis, Yiannis; Meili, Naika; Mijic, Ana; Butler, Adrian; Athanasios, Paschalis
Abstract: Globally, urban areas face multiple challenges owing to climate change. Urban greening (UG) is an excellent option for mitigating flood risk and excess urban heat. Rainwater harvesting (RWH) systems can cope with plant irrigation needs and urban water management. In this study, we investigated how UG and RWH work together to mitigate environmental risks. By incorporating a new RWH module into the urban ecohydrological model Urban Tethys-Chloris (UT&C), we tested different uses of intervention approaches for 28 cities in the USA, spanning a variety of climates, population densities, and urban landscapes. UT&C was forced by the latest generation convection-permitting climate model simulations of the current (2001–2011) and end-of-century (RCP8.5) climate. Our results showed that neither UG nor RWH, through the irrigation of vegetation, could significantly contribute to mitigating the expected strong increase in 2 m urban canyon temperatures under a high-emission scenario. RWH alone can sufficiently offset the intensifying surface flood risk, effectively enhance water saving, and support UG to sustain a strong urban carbon sink, especially in dry regions. However, in these regions, RWH cannot fully fulfill plant water needs, and additional measures to meet irrigation demand are required to maximize carbon sequestration by urban vegetation.